Edukasi Gosok Gigi Sebagai Upaya Pencegahan Karies Gigi di TK Tunas Islam Tamantirto, Kasihan, Bantul - Dwi Yati; Susanti, Dwi; Utami, Kristina Dias (JOURNAL OF PHILANTHROPY: The Journal of Community Service, 2026)
Dental caries in children is a common health problem, and one way to prevent it is to practice proper toothbrushing habits. This Community Service Activity (PKM) aims to educate children at Tunas Islam Kindergarten on how to brush their teeth correctly to prevent dental caries. The methods applied include interactive health education and filling out pretest and posttest questionnaires. A total of 30 children participated in educational activities that included theory and hands-on toothbrushing practice. The pre-test and post-test evaluations showed a significant increase in knowledge of toothbrushing techniques. Before education, 60% of children did not know the right technique; after education, 85% were able to demonstrate the correct understanding, indicating the success of education in improving their understanding. In addition, most children intend to practice the habit at home and teach it to their parents. This activity is expected to have a long-term impact on improving children's dental hygiene habits and strengthening public awareness of the importance of preventing caries from an early age.